2022
DOI: 10.1002/anie.202217220
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Perturbation of Copper Single‐Atom CO2Reduction Catalysts in a Molecular Way

Abstract: Fine‐tuning electronic structures of single‐atom catalysts (SACs) plays a crucial role in harnessing their catalytic activities, yet challenges remain at a molecular scale in a controlled fashion. By tailoring the structure of graphdiyne (GDY) with electron‐withdrawing/‐donating groups, we show herein the electronic perturbation of Cu single‐atom CO2 reduction catalysts in a molecular way. The elaborately introduced functional groups (−F, −H and −OMe) can regulate the valance state of Cuδ+, which is found to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 67 publications
1
34
0
Order By: Relevance
“…Duan et al reported that the introduction of new functional groups in Cu SACs supported on GDY derivatives can effectively change the electronic valence state of the metal active center atoms, thereby changing the selectivity of the catalyst to CH 4 in the CO 2 RR. 167 Cu SACs (Cu SA/R-GDY) with different functional groups (R, R = F, H, and OMe) showed a similar Cu metal loading of 12.8%, 12.3% and 13.4%, respectively. The δ value of Cu δ + in XANES is between 0 and +1, but the valence states of the different functional groups are also different.…”
Section: The Reaction Principle and Influencing Factors Of Co2rrmentioning
confidence: 99%
“…Duan et al reported that the introduction of new functional groups in Cu SACs supported on GDY derivatives can effectively change the electronic valence state of the metal active center atoms, thereby changing the selectivity of the catalyst to CH 4 in the CO 2 RR. 167 Cu SACs (Cu SA/R-GDY) with different functional groups (R, R = F, H, and OMe) showed a similar Cu metal loading of 12.8%, 12.3% and 13.4%, respectively. The δ value of Cu δ + in XANES is between 0 and +1, but the valence states of the different functional groups are also different.…”
Section: The Reaction Principle and Influencing Factors Of Co2rrmentioning
confidence: 99%
“…The strong interaction between CeO 2 and Cu promoted the adsorption and activation of CO 2 , boosting the activity and selectivity for CH 4 . Zou and co-workers demonstrated that modifying GDY with electron-withdrawing/-donating groups could indirectly regulate the electronic structure of Cu atoms (Figure f). Cu atoms on the F-substituted GDY exhibited the positive Cu δ+ centers, which accelerated water dissociation to promote the hydrogenation of intermediates toward the CH 4 production (Figure e).…”
Section: Ad Cu Catalysts For C1 Productsmentioning
confidence: 99%
“…Previous theoretical studies indicate the binding energy of *CO on Cu as the critical descriptor for further reduced species. , Protonation of *CO or the *CO dimerization will produce CH 4 or C 2 +, respectively. Different strategies, including crystal facet engineering, , size effect, , molecular functionalization, , alloying, , and defect-site surface modification, , have been employed to synthesize Cu-based catalysts for high selectivity to further reduced products. Monodispersed catalysts with spatially dispersed active sites can effectively suppress the *CO dimerization to favor electromethanation.…”
Section: Introductionmentioning
confidence: 99%
“…15,20 Duan et al observed that the faradaic efficiency (FE) of CH 4 can be effectively tuned by manipulating the electron density at the metal center. 15 With electron-withdrawing groups (−F) included, the selectivity of FE C>2e − / FE C2e − can reach as high as 9.33, 10.9 times higher than the electron-donating groups (−OMe). Chen and co-workers reported high faradaic efficiency (62.0%) of CO 2 to CH 4 with a corresponding current density of 153.0 mA cm −2 on singleatom Cu catalysts supported by porous Al 2 O 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation